The Concept of Constructiveness and its Fundamental Principles in Developing Teamwork Skills in Management - Dildora K. Sulaymanova (Goodwood Publishing, 2026)
Purpose: This study explores the socio-psychological characteristics of constructiveness in leadership and its role in fostering teamwork among young managers. This highlights the importance of constructive interactions in promoting effective leadership and collaboration within organizational settings. Research Methodology: This study adopts a qualitative and theoretical approach, analyzing the existing literature in management, psychology, and organizational behavior. It examines various models of interpersonal interaction and incorporates conflict management techniques to assess their effectiveness in fostering constructive team work. Results: The study revealed that constructiveness fosters effective teamwork by promoting transparent communication, trust, open dialogue, and collaborative decision-making. It also highlights that conflict management techniques, such as compromise and problem solving, significantly improve team cohesion and organizational performance. Conclusions: Constructiveness is fundamental to modern leadership, as it fosters a positive organizational environment, motivates employees, and ensures long-term organizational growth. By applying the principles of constructiveness, teams can improve their performance and resolve conflicts more efficiently. Limitations: The study’s findings are based on theoretical analysis, and empirical validation is required to assess the practical application of constructivity in real-world management scenarios. Contributions: This study contributes to our understanding of constructiveness as a fundamental managerial skill by linking emotional intelligence, strategic thinking, and leadership skills to team success.